Comparative mortality risks of antipsychotic medications in community-dwelling older adults. (July 2014) - Gerhard, T.; Huybrechts, K.; Olfson, M.; Schneeweiss, S.; Bobo, W. V.; Doraiswamy, P. M.; Devanand, D. P.; Lucas, J. A.; Huang, C.; Malka, E. S.; Levin, R.; Crystal, S.
Abstract : Background: All antipsychotic medications carry warnings of increased mortality for older adults, but little is known about comparative mortality risks between individual agents. Aims: To estimate the comparative mortality risks of commonly prescribed antipsychotic agents in older people living in the community. Method: A retrospective, claims-based cohort study was conducted of people over 65 years old living in the community who had been newly prescribed risperidone, olanzapine, quetiapine, haloperidol, aripiprazole or ziprasidone ( n = 136 393). Propensity score-adjusted Cox proportional hazards models assessed the 180-day mortality risk of each antipsychotic compared with risperidone. Results: Risperidone, olanzapine and haloperidol showed a dose–response relation in mortality risk. After controlling for propensity score and dose, mortality risk was found to be increased for haloperidol (hazard ratio (HR) = 1.18, 95% CI 1.06–1.33) and decreased for quetiapine (HR = 0.81, 95% CI 0.73–0.89) and olanzapine (HR = 0.82, 95% CI 0.74–0.90). Conclusions: Significant variation in mortality risk across commonly prescribed antipsychotics suggests that antipsychotic selection and dosing may affect survival of older people living in the community.